Methods of parallel computing for multilevel fuzzy Takagi – Sugeno systems - Yershov, S.V.; Ponomarenko, R.М.. (Інститут програмних систем НАН України, 2018)
Parallel tiered and dynamic models of the fuzzy inference in expert-diagnostic software systems are considered, which knowledge bases are based on fuzzy rules. Tiered parallel and dynamic fuzzy inference procedures are developed that allow speed up of computations in the software system for evaluating the quality of scientific papers. Evaluations of the effectiveness of parallel tiered and dynamic schemes of computations are constructed with complex dependency graph between blocks of fuzzy Takagi – Sugeno rules. Comparative characteristic of the efficacy of parallel-stacked and dynamic models is carried out.Problems in programming 2016; 2-3: 141-149